The intracellular domain of interferon-α receptor 2c (IFN-αR2c) chain is responsible for Stat activation - Kotenko, Serguei V. (The National Academy of Sciences, 1999)
Type I IFNs activate the Jak–Stat signal transduction pathway. The IFN-α receptor 1 (IFN-αR1) subunit and two splice variants of the IFN-αR2 subunit, IFN-αR2c and IFN-αR2b, are involved in ligand binding. All these receptors have been implicated in cytokine signaling and, specifically, in Stat recruitment. To evaluate the specific contribution of each receptor subunit to Stat recruitment we employed chimeric receptors with the extracellular domain of either IFN-γR2 or IFN-γR1 fused to the intracellular domains of IFN-αR1, IFN-αR2b, and IFN-αR2c. These chimeric receptors were expressed in hamster cells. Because human IFN-γ exhibits no activity on hamster cells, the use of the human IFN-γ receptor extracellular domains allowed us to avoid the variable cross-species activity of the type I IFNs and eliminate the possibility of contributions of endogenous type I IFN receptors into the Stat recruitment process. We demonstrate that Stat recruitment is solely a function of the IFN-αR2c intracellular domain. When chimeric receptors with the human IFN-γR1 extracellular domain and various human IFN-α receptor intracellular domains were expressed in hamster cells carrying the human IFN-γR2 subunit, only the IFN-αR2c subunit was capable of supporting IFN-γ signaling as measured by MHC class I induction, antiviral protection, and Stat activation. Neither the IFN-αR2b nor the IFN-αR1 intracellular domain was able to recruit Stats or support IFN-γ-induced biological activities. Thus, the IFN-αR2c intracellular domain is necessary and sufficient to activate Stat1, Stat2, and Stat3 proteins.